Integrasi Gaya Kepemimpinan Kolaboratif Dalam Lingkungan Pendidikan Pesantren (Studi Kasus SMP Islam Brawijaya Pungging) - Syafa'at, Wahyu (EDUSIANA: Jurnal Manajemen dan Pendidikan Islam, 2025)
This study explores the integration of collaborative leadership within the context of Islamic boarding school–based education, using SMP Islam Brawijaya Pungging as a case study. The main objective of this research is to examine how collaborative leadership is implemented by the school principal to foster a culture of cooperation among school stakeholders, including teachers, administrative staff, students, and parents, in order to improve educational quality and harmonize pesantren values. The research employed a qualitative approach using case study methodology, focusing the analysis on daily leadership practices and interactions within the school community. Data were collected through direct observation, in-depth interviews, and institutional documentation, and analyzed using thematic analysis techniques. Findings indicate that collaborative leadership enhances active participation across all school components, fosters a dialogic environment, and strengthens the institution’s identity based on Islamic values. The principal functions as a facilitator, guiding and accommodating various aspirations in strategic decision-making processes. This research contributes to the development of leadership models in Islamic boarding school environments by emphasizing the importance of synergy, openness, and collective participation. The study’s insights are expected to serve as a reference for similar institutions seeking to strengthen organizational effectiveness and the realization of value-based educational visions.